2019
DOI: 10.1021/acssynbio.9b00358
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Queues at ClpXP Increase Antibiotic Tolerance

Abstract: Antibiotic tolerance is a widespread phenomenon that renders antibiotic treatments less effective and facilitates antibiotic resistance. Here we explore the role of proteases in antibiotic tolerance, short-term population survival of antibiotics, using queueing theory (i.e., the study of waiting lines), computational models, and a synthetic biology approach. Proteases are key cellular components that degrade proteins and play an important role in a multidrug tolerant subpopulation of cells, called persisters. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…Hence, the sspB mutations probably influence ClpX-mediated degradation of several proteins and alter the expression of genes related to cellular stress. In agreement with our findings, ClpXP contributes to antibiotic tolerance and peptide resistance in different bacterial species (52,53). Extrusion of AMPs by an energy-dependent efflux system constitutes an important AMP resistance mechanism (54)(55)(56), and exposure to antibiotics and biocides can select for mutation-driven overexpression of efflux pumps in S. maltophilia (15,16,57).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, the sspB mutations probably influence ClpX-mediated degradation of several proteins and alter the expression of genes related to cellular stress. In agreement with our findings, ClpXP contributes to antibiotic tolerance and peptide resistance in different bacterial species (52,53). Extrusion of AMPs by an energy-dependent efflux system constitutes an important AMP resistance mechanism (54)(55)(56), and exposure to antibiotics and biocides can select for mutation-driven overexpression of efflux pumps in S. maltophilia (15,16,57).…”
Section: Discussionsupporting
confidence: 90%
“…To that end, results revealed that ClpP protease is upregulated 2.3-fold within wild-type, as opposed to YhaK-mutant cells. ClpPX has been shown to affect antibiotic tolerance during stress conditions in other Gram-negative pathogens, such as E. coli [51]. Regardless of the molecular mechanism(s), taken together, these results suggest that YhaK is likely to contribute to A. baumannii's AEMR phenotype.…”
Section: Rna Sequencing Of Wild-type and Yhak-mutant Cells During Gro...mentioning
confidence: 88%
“…While competition for shared transcriptional/translational resources represents a major source of context-dependence [15,16], it is only one of many such sources. For instance, the limited availability of degradation machinery [88][89][90][91] and the spatial arrangement and orientation of compositional context [12] can result in crosstalk among otherwise unrelated genes. Similarly, metabolic burden can negatively impact cellular growth rate [15,18,84,92,93], although its extent depends on experimental conditions [94][95][96] and may only be transient as it often disappears after several generations of exponential growth [16,97].…”
Section: Discussionmentioning
confidence: 99%